Legal Protection For Car Rental Owners In Rental Agreements - Nazar, Justin Al Hakim; Sukana Ishak, Ryan Rahma; Nurhabibi, Haikal; Karina, Siska; Handiriono, Raden (Jurnal Legisci, 2024)
A car rental agreement is a common type of agreement in society. The lease agreement binds the parties involved with their respective rights and obligations. However, these agreements are susceptible to default or negligence in fulfilling commitments, which can lead to injustice and require legal protection. This study focuses on analyzing the legal protection in car rental agreements against rental owners from a civil law perspective. The research method applied is based on normative law by collecting data from literature research and research to a rental place. After the relevant information is collected, analysis is carried out in three steps: searching for data, then presenting data, and finally making conclusions. The study's findings show that the lease agreement's protection is clearly regulated in Article 1320 of the Civil Code. Civil law regulates the rights and responsibilities of each party. If there is a default, the aggrieved party can send a warning letter called a summons. In addition, civil law also provides a framework for resolving disputes outside the court or through court proceedings. Thus, civil law provides a solid foundation for the implementation and settlement of disputes that may arise from car rental agreements, with the aim of maintaining justice and protecting car rental owners under the provisions that have been set.